Psychology of cleansing through the prism of intersecting object histories. (18th February 2021) - Ekves, Zachary; Prystauka, Yanina; Davis, Charles P.; Yee, Eiling; Altmann, Gerry T. M.
Abstract: We link cleansing effects to contemporary cognitive theories via an account of event representation (intersecting object histories) that provides an explicit, neurally plausible mechanism for encoding objects (e.g., the self) and their associations (with other entities) across time. It explains separation as resulting from weakening associations between the self in the present and the self in the past.